PENGEMBANGAN MATERI SIMAKAN BERBASIS KEARIFAN LOKAL UNTUK KELAS 1 SEKOLAH DASAR - Katarina Retno; Tresiana Sari Diah Utami (Universitas Katolik Musi Charitas, 2019)
Learning Indonesian in elementary schools is carried out with attention to language skills. The four language skills are listening, speaking, reading and writing skills. In practice, listening skills become skills that are rarely trained and / or implemented in an inappropriate way. This is caused by various things. One of them is listening learning carried out with material used for listening learning derived from textbooks published by certain publishers. Thus, the material may not accommodate local wisdom. This research is part of the development research carried out in stages. This research is the second stage of the five planned stages. At this stage, the research is carried out until the revision stage of the expert validation results. This article only discusses the results of expert validation in the material development section. The results showed that the learning material developed did not fully accommodate local wisdom. The validator gives advice relating to the content of material that can be developed in order to raise local wisdom and remain in accordance with the basic competencies used.